2011
DOI: 10.1038/onc.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

FZD7 has a critical role in cell proliferation in triple negative breast cancer

Abstract: Breast cancer is genetically and clinically heterogeneous. Triple negative breast cancer (TNBC) is a subtype of breast cancer that is usually associated with poor outcome and lack of benefit from targeted therapy. We used microarray analysis to perform a pathway analysis of TNBC compared with non-triple negative breast cancer (non-TNBC). Overexpression of several Wnt pathway genes, such as frizzled homolog 7 (FZD7), low density lipoprotein receptor-related protein 6 and transcription factor 7 (TCF7) was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
205
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(223 citation statements)
references
References 33 publications
11
205
0
1
Order By: Relevance
“…For instance, the pharmacological inhibition of Fzd7, which is frequently overexpressed in hepatocellular carcinoma (HCC), displayed anti-tumor properties by involving β-catenin and PKCδ signals [63] . Fzd7 was also crucial through the canonical Wnt pathway for cell proliferation and invasiveness in triple negative breast cancer cells as well as for tumor formation in xenograft models [64] . Moreover, the increased expression of Fzd4 through the up-regulation of β-catenin dependent Wnt signaling promoted in invasive glioma cells the acquisition of glioma stem cell-like properties and resistance to apoptosis [65] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%
“…For instance, the pharmacological inhibition of Fzd7, which is frequently overexpressed in hepatocellular carcinoma (HCC), displayed anti-tumor properties by involving β-catenin and PKCδ signals [63] . Fzd7 was also crucial through the canonical Wnt pathway for cell proliferation and invasiveness in triple negative breast cancer cells as well as for tumor formation in xenograft models [64] . Moreover, the increased expression of Fzd4 through the up-regulation of β-catenin dependent Wnt signaling promoted in invasive glioma cells the acquisition of glioma stem cell-like properties and resistance to apoptosis [65] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%
“…35 It has been shown that Fzd7 is upregulated in cancers 24 and inhibition of Fzd7 in cancer cells leads to decrease of cell growth 36 and tumor transformation. 2 Recognition of the importance Wnt signaling pathway mutations in some cancers has provided strong evidence that the pathway plays a major role in the genesis of some types of human cancers. 37 The findings suggested that targeting Fzd7 receptor and related signaling pathway molecules can be considered as a novel pharmacologic tool for caners therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of Wnt pathway genes such as low density lipoprotein receptor-related protein 6, frizzled homolog 7 (Fzd7), and transcription factor 7 (TCF7) is well documented in TNBC. 2 Over the past decade, our understanding and treatment of several types of breast cancers have improved but treatment of TNBC remained as a clinical unmet need Period 3 Frizzled (Fzd) proteins are receptor family of 7-pass transmembrane molecules comprising 10 members in humans. Fdzs consist of the N-terminal extracellular called cysteine-rich domain (CRD) 4,5 and intracellular C-terminal domain, including PDZ domain.…”
Section: Introductionmentioning
confidence: 99%
“…The canonical Wnt signalling pathway play an important role in cell proliferation and TCF/LEF mediated transcriptional activation on TNBC. 35,36 MDA-MB-231 is a highly invasive, "basal type" fibroblastic breast cancer cell line, 37 undergoes autocrine Wnt signaling which down regulates E-cadherin expression at cell-cell borders.…”
Section: Differential Effects Of Dvl2 and Dvl3 Knockdown In Canonicalmentioning
confidence: 99%